Management of Six Root Canals in Mandibular First Molar - Claudio Maniglia-Ferreira; Fabio de Almeida Gomes; Bruno Carvalho Sousa (Case Reports in Medicine)
Success in root canal treatment is achieved after thorough cleaning, shaping, and obturation of the root canal system. This clinical case describes conventional root canal treatment of an unusual mandibular first molar with six root canals. The prognosis for endodontic treatment in teeth with abnormal morphology is unfavorable if the clinician fails to recognize extra root canals.